Reversing to detect software vulnerabilities - Goncalves de Oliveira, Bruno; Vitali, Maycon; Watanabe, Willian Massami (2017 12th Iberian Conference on Information Systems and Technologies (CISTI), 2017)
Security is a real concern for the society and it is not different for software. Vulnerable applications can expose the users to multiple risks. Software disassembling is an interesting approach to discover vulnerabilities. Unmounting an application into Assembly code can reveal multiple characteristics from the software. During the disassembling, technical features can be revealed that enable the researcher to discover issues even with no source-code available. The paper has the goal of demonstratingSecurity is a real concern for the society and it is not different for software. Vulnerable applications can expose the users to multiple risks. Software disassembling is an interesting approach to discover vulnerabilities. Unmounting an application into Assembly code can reveal multiple characteristics from the software. During the disassembling, technical features can be revealed that enable the researcher to discover issues even with no source-code available. The paper has the goal of demonstrating the disassembling efficacy for detecting vulnerabilities on software and presents a case study to evaluate the concept. the disassembling efficacy for detecting vulnerabilities on software and presents a case study to evaluate the concept.